AFLATOXIN STANDARDS AND MAIZE TRADE - Papic Brankov, Tatjana; Jovanović, Marijana; Grujić, Biljana (Economics of Agriculture, 2013)
Mycotoxin contamination is recognized as an unavoidable risk in agriculture production in both developed and developing countries. Health consequences of aflatoxin are much more serious problem in developing countries than in developed. The number of countries regulating aflatoxins has significantly increased over the years. In paper were discussed different limitations for aflatoxin in the world, as well as their relation to the global maize trade. Following the debate in Serbia, caused by various aflatoxin regulations in different years, we wanted to contribute to the establishment of the state policy that targets mentioned issue. One of main conclusions in paper is that nations with strong trade connections tend to have similar regulations on allowed level of aflatoxin within the maize. Also, it was concluded that incidental appearance of Aspergillus flavus in maize during 2012 in Serbia demonstrates the weakness of the control system, as well as weakness of the national legislation. Main recommendation is oriented to limitation of aflatoxin B1in animal feed, what is in same time the most effective measure for control of level of aflatoxin M1 in milk. After completing this condition Serbia has to return back the allowed limit for aflatoxin in milk at level of 0,05 µg/kg.